Please answer this
Attachments:
![](https://hi-static.z-dn.net/files/df5/c8af6fd7d61c056e58051c0b5e276989.jpg)
Answers
Answered by
1
Answer:
f(x)+g(x)=0
a, (x²+ax+2)+(x²+2x+a)=0
a, x²+ax+2+x²+2x+a=0
a, 2x²+2x+ax+a=0
a, 2x(x+1)+a(x+1)=0
a, (2x+a)(x+1)=0
so, 2x+a=0
a, 2x=-a
a, x=-a/2
or, x+1=0
a, x=-1
therefore,f(x)+g(x)=(-1)+(-1)
=-1-1=-2
or, f(x)+g(x)=(-a/2)+(-a/2)
=-2a/2=-a
Similar questions
English,
5 months ago
English,
5 months ago
Computer Science,
10 months ago
Chemistry,
1 year ago
Biology,
1 year ago